Qualidade de solos em diferentes coberturas vegetais no bioma Mata Atlântica - ES - Rodrigues, Aline Alves (2019)
The dissertation was divided into three chapters and analyzed how the physical, chemical and biological attributes are influenced by land use and how they influence the existing vegetation in the Atlantic Forest Biome site in Espírito Santo. The first cha